Analytic hierarchy process for evaluating the quality of courier services in e-commerce services from the perspective of Pos Indonesia Purwokerto - Jihad Sindhu Gossa; Khairun Nisa Meiah Ngafidin; Sisilia Thya Safitri (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2023)
E-commerce became one of the technological developments in Indonesia in the fourth industrial revolution. Since then, the daily needs transaction process has become accessible through the e-commerce platform. The rapid development of e-commerce is predicted to increase and thus encourage the development of courier services over the past period, making courier services an essential element that affects customer satisfaction in e-commerce services. An analysis of customer satisfaction in several e-commerce service providers towards customer reviews on Google Play conducted by Sasmita and a statement by the Ministry of Trade through a consumer complaint report in 2021 stated that complaints about problems in the e-commerce sector have increased, which includes courier services incorporated with e-commerce service providers. Gulc argued that at least seven factors determine the quality of courier service based on the customer's perspective. The AHP method assists courier services affiliated with e-commerce services in recognizing which of these seven factors of courier service quality dimensions require attention to create a sustainable competitive advantage. This research aims to measure the priority level of criteria in determining the quality of courier services on e-commerce platforms, thus providing recommendations for the appropriate service priorities for courier service companies. The calculation results using AHP on the seven factors determining the quality of courier service according to the Manager Assistant of the Service Department at the Central Purwokerto Branch of the Kantor POS Indonesia show that the responsiveness criterion is more important than the other six criteria.